THE REFERENTIAL MEANING OF DEIXIS REVEALMENT IN ARABIC-ENGLISH AR RAHMAN - Nindy Dwi Febriana; I Wayan Resen; Putu Devi Maharani (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
According to an article in Detik News, Quran Surah Ar Rahman is the one of the names of Quran surah is written in the language of Arabic, Ar Rahman also is belong to the 55th of 114th sub-chapter of the Quran. Ar Rahman goes by 78 verses/sentences of God message that fundamental for human and living creatures in the life and afterlife. This study is corcerned with deixis revealment in the first step, and then the reference meaning will come after it. It is used a descriptive qualitative  method to identify the data. The types of deixis of English Translation of Ar Rahman are found to apply by using a theory about kind of deixis proposed by Levinson (1983:62) and Yule (1996:12). Apart from that, in completing this study, next the reference meaning were interpreted under a theory of reference meaning from the same linguist proposed by Yule (1996). This study is under the reason to determine kinds of deixis found in each English verses/sentences of Ar Rahman, and to avoid the ambiguous meaning are represented by the reference of Ar Rahman’s interpretation connected to the context of the utterance. The references meaning in this study, which was proven by some representatives data included: Person  Deixis, Place Deixis, Social Deixis, Discourse Deixis, and Time Deixis. This study found person deixis dominated in highest percentage and followed by the next the numeral sequence are place deixis, social deixis, time deixis, and discource deixis in smallest percentage. The writer found 62 data occurrences of deixis and they have followed by the reference meaning. The types of deixis found in the Ar Rahman are consisting of 33 data of person deixis (53,2%), 13 data of place/spatial deixis (21%), 10 data of social deixis (16.1%), 1 data of discourse deixis (1,6%), and 5 data of time/temporal deixis (8,1%).